Synthesis and characterization of allyl fatty acid derivatives as reactive coalescing agents for latexes - Joana V. Barbosa (2012)
This work evaluated the use of allyl fatty acid esters derived from vegetable oil (palmitic acid, soybean and sunflower oils) as reactive coalescing agents in a waterborne latex system. Allyl fatty acid derivatives (AFAD) from vegetable oils were synthesized by two different processes. The synthesis was monitored by IR-spectroscopy and the final product characterized by FT-IR, GC-MS, H-1 and C-13 NMR. The presence of conjugated double bonds in the aliphatic chain was confirmed, which is a determinant for the proposed autoxidative latexes drying mechanism. Each of the AFAD were subsequently added to a standard acrylic emulsion, in order to study its potential as reactive coalescing agent. The minimum film-forming temperature (MFT), glass transition temperature (T (g)), drying time and rubbing resistance to solvents were evaluated. The results showed that, when added to water-borne acrylic resins, an AFAD acts as a non-volatile plasticizer capable of autoxidative crosslinking with itself.